2012
DOI: 10.1111/j.1471-4159.2012.07883.x
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine prevents oligodendrocyte and myelin loss and promotes maturation of oligodendrocyte progenitors in the hippocampus of global cerebral ischemia mice

Abstract: White matter impairment is a feature of vascular depression. The anti‐psychotic quetiapine has been shown to enhance the therapeutic effects of anti‐depressants on vascular depression, but the mechanism remains unknown. In this study, we found that 2 weeks of treatment with quetiapine prior to bilateral carotid artery occlusion and reperfusion, in an animal model of vascular depression, resulted in reduced myelin breakdown and oligodendrocyte loss compared to placebo‐treated mice on post‐operative day (POD) 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 21 publications
5
33
0
2
Order By: Relevance
“…QUE, OLA, and HAL promoted differentiation of OPCs into CNP positive oligodendrocytes in a dose-dependent manner, but had no effect on OPC proliferation. These findings are consistent with previous studies in which QUE was found to facilitate NPC development into oligodendrocyte lineage cells in vitro and promote maturation of oligodendrocytes in vivo (Bi et al, 2012;Zhang et al, 2012). We also found that the differentiation-inducing effects of APDs are associated with the increased expression of Olig1 and Olig2, two oligodendroglial transcription factors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…QUE, OLA, and HAL promoted differentiation of OPCs into CNP positive oligodendrocytes in a dose-dependent manner, but had no effect on OPC proliferation. These findings are consistent with previous studies in which QUE was found to facilitate NPC development into oligodendrocyte lineage cells in vitro and promote maturation of oligodendrocytes in vivo (Bi et al, 2012;Zhang et al, 2012). We also found that the differentiation-inducing effects of APDs are associated with the increased expression of Olig1 and Olig2, two oligodendroglial transcription factors.…”
Section: Discussionsupporting
confidence: 93%
“…There is also in vivo evidence supporting this viewpoint. For example, OLA treatment resulted in increased oligodendrocyte lineage cells in hypothalami of mice (Yamauchi et al, 2012); the regeneration or maturation of oligodendrocytes was significantly promoted by chronic treatment of QUE both in cuprizone-induced demyelinated mice and in global cerebral ischemia mice (Bi et al, 2012). The present study provides direct evidence that both atypical APDs and typical APDs promoted the differentiation of OPCs into CNP-positive oligodendrocytes in culture.…”
Section: Discussionsupporting
confidence: 55%
“…The specific effects of antidepressant medication on white matter microstructure are unclear; however, an animal study indicates they may prevent oligodendrocyte and myelin loss. 39 As such, antidepressant medications may mediate changes to FA in patients with MCI-MD. Furthermore, the sample included both men and women with a broad age range.…”
Section: Limitationsmentioning
confidence: 99%
“…There is an increase in differentiation of rodent progenitor cells into oligodendrocytes and a greater extent of myelination in cortical aggregate cultures after treatment with quetiapine [75]. Moreover, findings from in vivo experimental models demonstrate reduced demyelination and loss of oligodendrocytes [76, 77] with quetiapine treatment, as well as faster return of myelin proteins [78]. These data suggest that quetiapine enhances remyelination in experimental models, raising hopeful possibilities for the related compound dimethyl fumarate in humans.…”
Section: Promoting Remyelination—potential Candidate Drugsmentioning
confidence: 99%